Comparable Outcomes in Early Hepatocellular Carcinomas Treated with Trans-Arterial Chemoembolization and Radiofrequency Ablation - Benjamin Wei Rong Tay; Daniel Q. Huang; Muthiah Mark; Neo Wee Thong; Lee Guan Huei; Lim Seng Gee; Low How Cheng; Lee Yin Mei; Prem Thurairajah; Lim Jia Chen; Cheng Han Ng; Wen Hui Lim; et al. (Biomedicines, 2022)
The guidelines recommend radiofrequency ablation (RFA) for early hepatocellular carcinomas that are less than 3 cm and trans-arterial chemoembolization (TACE) for intermediate-stage tumors. Real-world patient and tumor factors commonly limit strict adherence to the guidelines. We aimed to compare the clinical outcomes for TACE and RFA in early HCC. All consecutive patients from 2010 to 2014 that were treated with locoregional therapy at our institution were enrolled. The decision for TACE or RFA was based on tumor location, stage and technical accessibility for ablation. A subgroup analysis was performed for patients with tumors less than 3 cm. A total of 168 patients underwent TACE while 56 patients underwent RFA. Patients treated with TACE and RFA had 1- and 5-year survival rates of 84.7% and 39.8% versus 91.5% and 51.5%, respectively (p = 0.28). In tumors less than 3 cm, there was no significant difference in overall survival (p = 0.69), time to progression (p = 0.55), or number of treatment sessions required (p = 0.12). Radiofrequency ablation had a significantly higher chance of a complete response (p = 0.004). In conclusion, TACE may be selectively considered for early-stage hepatocellular carcinoma in patients unsuitable for other modalities.